Respiratory Disease and its Management - McLuckie, A. (Competency-Based Critical Care,, 2009)
Recent advances in training for Intensive Care Medicine (ICM) have led to the introduction of competency based training, with a strong focus on the development of specific competencies at basic, intermediate and advanced stages of learning. This ensures trainees hold the appropriate skills and knowledge to undertake safe clinical practice, and thus provide good patient care. Respiratory Disease and its Management covers key topics, specific to the area of respiratory disease, that are addressed in the ICM training module. Issues range from conditions and illnesses such as asthma and pneumonia to treatments including ventilatory support and Inspired and Expired Gas Monitoring. Written by recognised experts in their subject area, and edited by Angela McLuckie, FRCA FJFICM Lead Clinician and Consultant Intensivist at Guy's and St Thomas' NHS Trust, London, UK, this book provides the reader with a compendium of knowledge and information. This book will be of special interest to critical care trainees, and will also appeal to nursing, pharmacy and physiotherapy staff.